PREVALENCE OF TRAUMATIC INJURIES CAUSING NON VITALITY OF TOOTH LEADING TO ROOT CANAL TREATMENT - A RETROSPECTIVE ANALYSIS - Harikrishnan, Reshma; Ranjan, Manish; Ganesh. S, Balaji (International Journal of Psychosocial Rehabilitation, 2020)
Traumatic dental injuries are impact injuries that occur due to external factors. It is frequent and unavoidable. These injuries are more common in younger age groups, particularly in children and adolescence. Males are more prone to these dental injuries than females. Anterior teeth are the most affected. Few of the complications of these injuries include pulp necrosis, infection, internal resorption, apical periodontitis, disturbances in root development, etc. Pulp vitality tests are done to examine the presence of blood flow. Treatments for traumatic dental injuries depend on the severity of the injury. Re-implantation of the tooth, restoration of the fractured tooth, root canal treatment, crowns, extractions, etc. The aim of this study is to assess the association between traumatic dental injuries that lead to root canal treatments and gender. A retrospective study was done in an institutional setting. A sample size 872 was taken into consideration. All patients who underwent root canal treatment in the time frame of June 2019 – April 2020. Only anterior teeth that underwent trauma and required RCT were taken into account. The patients detailed case sheets were evaluated. Collected data was imported into SPSS software for data analysis. The total number of patients involved in the study was 289, out of which 76.4% (220 patients) were males and 23.6% were females. Ellis Type II and Type III fractures were taken into account. 13.9% (40 patients) were diagnosed with Ellis type II fracture and 86.1% (248 patients) were diagnosed with Type III fractures. Majority of the patients (96.5% - 278 patients) had undergone RCT as their treatment and the remaining 3.5% had LCR restorations done. A cross analysis between age and Ellis fracture was done. Majority of the patients were prone to getting a dental injury in the age group of 21-40, for both Type II and Type III fractures. (p value< 0.05= significant) The cross analysis between gender and Ellis fracture showed that male patients were higher in number for both type II (23 patients) and Type III (197 patients). (p value < 0.05= significant). Young males are more prone to traumatic dental injuries as compared to females. There were higher chances of the injury leading to a Root Canal Treatment in both Type II and III Ellis fractures.